Developing leadership among the gifted children in the elementary school - Ordillas, Aurea Umipig 1926- (College of Education, University of the Philippines Diliman, 1968)
The study looked into the nature and development of leadership among gifted children in the elementary school. Literary resources were explored in getting deeper understanding of the rationale behind the teaching of leadership. This in turn, has given direction to the search for teaching-learning experiences that will develop leadership among the gifted in the elementary school. Findings show that leadership can be developed among gifted children in the elementary school. Provision of a favorable environment for leadership training activities is the school's major function if it is to perform its role as the greatest source of leaders and as an agent of social change.